A lei do mar do Ceará como via para uma sustentabilidade forte no contexto da economia azul - Lima, Maria Cecília Girão Veras (2023)
The blue economy is a new terminology used in the context of the economy linked to the ocean and, given the “race to the sea in the Anthropocene” of nations due to the scarcity of natural resources, it is considered one of the new frontiers of the 21st century. Given the close relationship between legal and economic sciences, this interdisciplinary research proves to be important as there is just a few legal research in Brazil aimed at establishing points of intersection between Economics and Law, perhaps dealing with the blue economy, a concept that highlights, at its core, the social aspect of the sea economy. As the blue economy deals with the relationship between economic, environmental and social approaches, the research establishes concepts such as sustainable development and sustainability, indicating Klaus Bosselmann's studies as a theoretical framework, especially regarding his version of strong sustainability. The methodology used was qualitative and deductive, starting from more general data to arrive at a specific examination of the Ceará ́s Sea Law and the instruments for managing marine resources in the state of Ceará, in addition to being exploratory, as it is a new theme, not yet consolidated in the scientific community. The blue economy is the context in which the analysis of the State Policy for the Conservation and Use of Marine Resources of the State of Ceará (CE), or Ceará ́s Sea Law, is developed. The general objective of this research is to investigate whether the Ceará ́s Sea Law contributes to strong sustainability in a possible blue economy situation in the state. The conclusions point towards adapting the Ceará standard to the possibility of a blue economy in Ceará, imbued with strong sustainability and social equity.